Designing Mixed-Signal PLLs regarding Multiple Requirements taking Non-Ideal Effects into Account - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))

Inductive Locating Method to Locate Miniaturized Wireless Sensors within Inhomogeneous Dielectrics - Lange, Sven; Schroder, Dominik; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))

A modular, scalable open-hardware platform for project-based laboratory courses in electrical engineering studies - Hetkämper, Tim; Krumme, Matthias; Dreiling, Dmitrij; Claes, Leander (SEFI 48th Annual Conference Proceedings - Engaging Engineering Education)

Je höher qualifiziert, desto besser? Rezeptive Phrasemkompetenzen von Französischlernenden

Das Smartphone in der berufsvorbereitenden Bildung junger Erwachsener. Empirische Erkundungen aus praxistheoretischer Perspektive - Dehmel, Lukas; Zick, Sebastian (Praxistheoretische Perspektiven in der Medienpädagogik)

Medienpädagogisches Erwachsenenbildungspersonal und Mediatisierung. Konzeptionelle Überlegungen zur theoretischen Erfassung biografischer Bearbeitungsprozesse - Dehmel, Lukas (Zeitschrift MedienPädagogik 37)

Vergissmeinnicht! Self-Tracking-Apps auf dem Smartphone als Erinnerungsräume junger Erwachsener - Dehmel, Lukas; Burgfeld-Meise, Bianca (MerzWissenschaft)

Refill friction stir spot and resistance spot welding of aluminium joints with large total sheet thicknesses (III-1965-19) - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Refill friction stir spot welding (RFSSW) is a highly flexible and promising solid-state joining method for aluminium alloys. Alternatively, resistance spot welding (RSW) can be stated as an appropriate joining method which can be automated and used within a high-volume production due to short process times. Both processes do not need any additional elements and a flat surface on both sides of the joints can be realised. In order to meet the modern requirements for crash safety and structural stiffness, thermal and mechanical joining methods are mainly combined by using single-component epoxy resin adhesives. Due to an insufficient knowledge about the application of both thermal joining methods for the abovementioned material combinations combined with additional adhesives, deeper investigations were done regarding the interactions of the polymers and the joining processes. Starting with a brief presentation of the boundary conditions of the investigations and the refill friction stir spot welding and resistance spot welding of high-strength aluminium alloys with sheet thicknesses bigger than 5.8 mm, the paper introduces the process-related joint properties of friction-based and resistance-based welded joints. Afterwards, the paper discusses the influences of the process parameter on the metallographic joint formation and load-bearing capacities for a selected two-sheet and four-sheet material combination. When combining the spot welding technologies with adhesives, the process parameters of the RFSSW process have to be adapted for the two-sheet combination by adding a squeeze-out step, while for RSW, just the preholding time has to be increased. Different challenges for both joining methods are shown. For RFSSW, the gap formation has to be considered when welding big total sheet thicknesses, while for RSW, the shape of the weld nugget is more important for an appropriate joint performance. Additionally, process optimisations for less adhesive incineration will be discussed for both joining processes, and the influences of the adhesive on the joint formation will be addressed with the help of load-bearing capacity evaluations. The paper closes with specific recommendations for the realisation of refill friction stir and resistance spot-welded joints with and without adhesive in the field of Al joints with big total sheet thicknesses which meet the quality demands and an outlook for further research steps will be given.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Early stage crack detection in mechanically joined steel/aluminum joints by condition monitoring - Gollnick, Maik; Giese, Patrick; Hein, David; Meschut, Gerson; Herfert, Daniel (Materials Testing)
Monitoring systems for machines, plants, materials and equipment are increasingly used in production processes. These online condition monitoring systems can detect damage or excessive loads at an early stage and can drastically reduce or prevent long downtimes of plants and machines as well as high repair and maintenance costs. This paper depicts a method for online crack detection with pattern recognition methods for specimens joined by self-pierce riveting under cyclic load in fatigue tests (laboratory application). A software specially conceived for this application was developed. This software, AnrissMF, uses active acoustic testing with a structure-borne sensor to detect cracks in the joints at a very early stage. It is shown in this paper that this software can detect cracks much earlier than classical failure criteria for joints (i. e. before any drop in stiffness or frequency is observed). Furthermore, the successful application of software AnrissMF for online crack detection during the fatigue strength test is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Process characteristics and influences of production-related disturbances in resistance element welding of hybrid materials with steel cover sheets and polymer core - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Raczkowski, Felix; Shnayien, Mary; Weich, Andreas; Wippich, Uwe
Die Autor*innen werfen einen medienwissenschaftlichen Blick auf die Online-Lehre des Sommersemsters 2020. Dabei betrachten sie unter anderem den Unterschied von klassischen Hörsälen zu den neuen, virtuellen Lernräumen, die aber auch physische Elemente beinhalten. Dabei regen sie an, den Einsatz von Lehr-Lern-Plattformen kritisch zu diskutieren und insgesamt die Lehre mit andauernder Medienreflexion zu begleiten. Ein zentraler Punkt des Papiers ist das Aufzeigen von Inklusions- und Exklusionspotenzialen von Online-Lehre. Vermeintliche Selbstverständnisse spielen hier eine Schlüsselrolle. So wird zum Beispiel häufig eine gewisse technische Infrastruktur seitens der Studierenden vorausgesetzt, die nicht immer vorhanden ist. Andererseits entfallen physische Barrieren, die in Lehrgebäuden vorhanden wären. Die Autor*innen mahnen, bei der Konzeption von Online-Lehre zu vermeiden, nicht-behinderte Personen als die Norm anzunehmen und stattdessen von verschiedenen Körperlichkeiten her zu denken, um die positive Potenziale dieses Lehrmodus zu nutzen. Das Diskussionspapier widmet sich auch ausführlich dem Einsatz von (digitalen) Tools, die weniger als Werkzeuge, denn als Medien der Lehre verstanden werden.

Lehre unter besonderen Bedingungen. Leitfaden zur temporären Umstellung der Lehre auf Online-Formate - Heinke, Christian; Shnayien, Mary; Sprenger, Florian; Wippich, Uwe (-)
Die vorübergehende Umstellung der Lehre von Präsenz- auf alternative Formate (sowohl online als auch offline) ist nicht nur eine logistische Herausforderung, sondern hat auch eine medientheoretische und eine wissenschaftspolitische Dimension. Gerade als Medienwissenschaftler_innen sollten wir in dieser Hinsicht reflektiert vorgehen, denn wir haben es mit einer Frage der Übersetzbarkeit von Inhalten zwischen unterschiedlichen Medien zu tun. Der Versuch, Lehrinhalte vom Medium des Sprechens und Diskutierens vor Ort in das Medium etwa einer Konferenzschaltung oder einer kollaborativen schriftlichen Textkommentierung zu übersetzen, verändert diese Inhalte. Wenn wir neue Formate für die Lehre unter besonderen Bedingungen ausprobieren, sollten wir uns die medienwissenschaftliche Prämisse, dass das Medium die Botschaft ist, ständig vor Augen halten. Deshalb schlagen wir vor, diese Aufgabe als ein medienwissenschaftliches Experiment zu betrachten und dieses Experiment im kommenden Semester nicht nur zum Medium, sondern auch zum Inhalt unserer Seminare zu machen.

Explorations in Digital Cultures
Digital media are transformative: they (re)shape the ways of communicating, relating, doing, knowing, and living as much as they are themselves subject to continuous transformation. The contributions in this volume explore these contemporary shifts in and of digital cultures by analyzing a wide range of topics: from data, infrastructures, algorithms, logistics, economies, politics, identities, collectives […] It’s Open Access! Check it out!

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf. - Heisler, Dietmar; Schemmer, Susanne (BWP@ Berufs- und Wirtschaftspädagogik - online)
Jugend wird als eine eigenständige Lebens- und Entwicklungsphase betrachtet. Für junge Geflüchtete stellt sie eine besondere Herausforderung dar. Für sie geht es nicht nur um die Bewältigung alterstypischer Entwicklungsaufgaben, sondern auch um eine gelingende Integration in die Aufnahmegesellschaft. Dazu gehören u. a. das Kennenlernen und die Aneignung von Sprache, Kultur und Werten, genauso die Erschließung von Alltagsräumen und Lebenswelten, z. B. von Freizeitmöglichkeiten, Bildung und von beruflichen Erfahrungsräumen. Die Frage zur gelingenden Integration und Gestaltung von Lebenswelten junger Geflüchteter wurde im Kontext der wissenschaftlichen Begleitung des Projekts „angekommen in Deiner Stadt“ der Walter Blüchert Stiftung genauer untersucht. Der Beitrag referiert u. a. die Ergebnisse einer in diesem Kontext durchgeführten egozentrierten Netzwerkanalyse. Die Ergebnisse zeigen, dass die Angebote den Rahmen für den Aufbau und die Erweiterung kommunikativer, sozialer Netzwerke darstellen und lebensweltliche Zugänge öffnen.
Keywords: Jugend; Lebensweltorientierung; soziale Netzwerke; geflüchtete Jugendliche; Lebenslagen junger Geflüchteter und Zugewanderter

Digitalisierung der Berufs- und Arbeitswelt. Herausforderungen und Potenziale in der Aus- und Weiterbildung für Geringqualifizierte, Un- und Angelernte - Heisler, Dietmar (Digitalisierung über berufliche Bildung gestalten.)
„Digitalisierung“ und die oft analog benutzten Begriffe „Industrie 4.0“, „Arbeit 4.0“ usw., gelten als zentrale, aktuelle Entwicklungen in Deutschland. Gemeint ist damit der Einzug moderner Informations- und Kommunikationstechnologien, insbesondere des Computers, des Internets, von funkbasierten Überwachungssystemen, Steuerungs- und Netzwerktechnologien, z.B. RFID und Bluetooth, von mobilen Technologien bzw. Endgeräten usw., in die Berufs- und Arbeitswelt, in Dienstleistung und Produktion. Begleitet wird dies durch eine zunehmende Miniaturisierung von Technologien, die Ausstattung von Gegenständen mit einer eigenen Intelligenz (smart products) und die Vernetzung dieser Gegenstände zu cyber-physischen Systemen (CPS). Der Beitrag befasst sich mit der Frage, welche Potenziale, aber auch welche Risiken der digitale Wandel sowie die Digitalisierung von Aus- und Weiterbildung für Menschen birgt, die am Arbeitsmarkt als Geringqualifizierte, als Un- und Angelernte gelten. Es wird davon ausgegangen, dass gerade diese Menschen vom digitalen Wandel in besonderem Maße betroffen sein werden. Es ist zu erwarten, dass es durch den digitalen Wandel zu neuen Segmentierungen, zu neuen Ausschluss- und Benachteiligungsmechanismen kommt, von denen Geringqualifizierte und auch andere marginalisierte und benachteiligte Menschen am Arbeitsmarkt und in der beruflichen Bildung betroffen sein werden. Der Aus- und Weiterbildung wird eine besondere Bedeutung beigemessen, um diesen Menschen die Teilhabe und Mitgestaltung des digitalen Wandels zu ermöglich.
Keywords: Digitalisierung; Geringqualifizierte; Weiterbildung; Un- und Angelernte

Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung

RESIlienz durch Helfernetzwerke zur BEwältigung von KriSen und Katastrophen - RESIBES : Schlussbericht zum Verbundprojekt : Teilvorhaben: Entwicklung und Bewertung von kommunikativen und organisatorischen Verfahren zur Etablierung eines Helfernetzwerkes - Hälterlein, Jens

Die Prognose sicherheitsrelevanter Ereignisse mittels Künstlicher Intelligenz. Zukunftsvorstellungen, Erwartungen und Effekte auf Praktiken der Versicherheitlichung - Hälterlein, Jens (BEHEMOTH. A Journal on Civilisation)

"Manche wissen halt einfach echt nicht, wie Studieren funktioniert, hat man das Gefühl" - Kontextuelle Dimensionen und Orientierungen studentischen Medienhandelns - Mojescik, Katharina; Engemann, Mario; Limpinsel, Inga; Lewandowski, Kira; Aßmann, Sandra (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

ABC: ABseits des Curriculums - Non-formales und informelles Lernen ab dem 1. Semester forschend erfassen - Aßmann, Sandra; Steffens, Yannic; Engemann, Mario; Blome, Andrea (Forschendes Lernen an Universitäten. Prinzipien, Methoden, Best Practices an der Ruhr-Universität Bochum)

Die Erforschung studentischen Medienhandelns mit der dokumentarischen Methode. Forschungsleitende Grundannahmen und forschungspraktische Umsetzung - Pensel, Sabrina; Mojescik, Katharina; Aksoy, Filiz; Engemann, Mario; Lewandowski, Kira (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

All-in-One - Hochschulkontexte studiengerecht und digital gestalten durch einen ganzheitlichen Onboarding-Prozess - Limpinsel, Inga; Neuberger, Olga; Aßmann, Sandra; Engemann, Mario (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

Einbindung Studierender bei der Erforschung studentischen Medienhandelns - Mojescik, Katharina; Pensel, Sabrina; Schick, Sarah; Engemann, Mario (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi V.; Wilhelm, René; Schmidt, Wolf G. (Journal of Computational Chemistry)

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Vibrational Raman spectroscopy on adsorbate-induced low-dimensional surface structures - Speiser, Eugen; Esser, Norbert; Halbig, Benedikt; Geurts, Jean; Schmidt, Wolf Gero; Sanna, Simone (Surface Science Reports)

Detector-Agnostic Phase-Space Distributions - Sperling, Jan; Phillips, D. S.; Bulmer, J. F. F; Thekkadath, G. S.; Eckstein, A.; Wolterink, T. A. W.; Lugani, J.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; et al. (Physical Review Letters)

Quantum photonics with active feedback loops - Engelkemeier, M.; Lorz, L.; De, Syamsundar; Brecht, Benjamin; Dhand, I.; Plenio, M. B.; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Molecular doping in few-molecule polymer-dopant complexes shows reduced Coulomb binding - Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Coulomb binding energy is reduced when a few-molecule integer charge transfer complex (ICTC) is formed.
Keywords: Materials Chemistry; General Chemistry

Efficient Bosonic Condensation of Exciton Polaritons in an H-Aggregate Organic Single-Crystal Microcavity. - Ren, J; Liao, Q; Huang, H; Li, Y; Gao, T; Ma, Xuekai; Schumacher, Stefan; Yao, J; Bai, S; Fu, H (Nano Letters)

Formation dynamics of exciton-polariton vortices created by nonresonant annular pumping - Berger, Bernd; Schmidt, Daniel; Ma, Xuekai; Schumacher, Stefan; Schneider, Christian; Höfling, Sven; Assmann, Marc (Physical Review B)

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Circular polarization reversal of half-vortex cores in polariton condensates - Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Spiraling vortices in exciton-polariton condensates - Ma, Xuekai; Kartashov, Yaroslav V.; Gao, Tingge; Torner, Lluis; Schumacher, Stefan (Physical Review B)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Externally controlled Lotka-Volterra dynamics in a linearly polarized polariton fluid - Pukrop, Matthias; Schumacher, Stefan (Physical Review E)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Toward Efficient Toxic-Gas Detectors: Exploring Molecular Interactions of Sarin and Dimethyl Methylphosphonate with Metal-Centered Phthalocyanine Structures - Aldahhak, Hazem; Powroźnik, Paulina; Pander, Piotr; Jakubik, Wiesław; Dias, Fernando B.; Schmidt, Wolf Gero; Gerstmann, Uwe; Krzywiecki, Maciej (The Journal of Physical Chemistry C)

Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Tetracene Ultrathin Film Growth on Hydrogen-Passivated Silicon - Niederhausen, Jens; MacQueen, Rowan W.; Lips, Klaus; Aldahhak, Hazem; Schmidt, Wolf Gero; Gerstmann, Uwe (Langmuir)

Photochemical Ring Opening of Oxirane Modeled by Constrained Density Functional Theory - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (ACS Omega)

Carrier-wave population transfer in semiconductors - Zuo, R; Song, X; Meier, Torsten; Yang, W (Journal of Physics: Conference Series)

Investigation of influencing parameters on the joint formation of the self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Lechner, Michael; Bobbert, Mathias; Meschut, Gerson; Merklein, Marion

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

罗铮 译.“大数据资本主义时代的马克思（Karl Marx in the Age of Big Data Capitalism) - Fuchs, Christian (世界社会主义研究年鉴 (World Socialism Research Yearbook 2020))

罗铮 译.“大数据资本主义时代的马克思（Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (国外理论动态（Foreign Theoretical Trends) 2020 (4))

Preface to Manfred Knoche’s Article “Science Communication and Open Access: The Critique of the Political Economy of Capitalist Academic Publishers as Ideology Critique” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cellulose Nanocrystal-Templated Tin Dioxide Thin Films for Gas Sensing - Ivanova, Alesja; Frka-Petesic, Bruno; Paul, Andrej; Wagner, Thorsten; Jumabekov, Askhat N.; Vilk, Yury; Weber, Johannes; Schmedt auf der Günne, Jörn; Vignolini, Silvia; Tiemann, Michael; Fattakhova-Rohlfing, Dina; Bein, Thomas (ACS Applied Materials & Interfaces)
Porous tin dioxide is an important low-cost semiconductor applied in electronics, gas sensors, and biosensors. Here, we present a versatile template-assisted synthesis of nanostructured tin dioxide thin films using cellulose nanocrystals (CNCs). We demonstrate that the structural features of CNC-templated tin dioxide films strongly depend on the precursor composition. The precursor properties were studied by using low-temperature nuclear magnetic resonance spectroscopy of tin tetrachloride in solution. We demonstrate that it is possible to optimize the precursor conditions to obtain homogeneous precursor mixtures and therefore highly porous thin films with pore dimensions in the range of 10–20 nm (ABET = 46–64 m2 g–1, measured on powder). Finally, by exploiting the high surface area of the material, we developed a resistive gas sensor based on CNC-templated tin dioxide. The sensor shows high sensitivity to carbon monoxide (CO) in ppm concentrations and low cross-sensitivity to humidity. Most importantly, the sensing kinetics are remarkably fast; both the response to the analyte gas and the signal decay after gas exposure occur within a few seconds, faster than in standard SnO2-based CO sensors. This is attributed to the high gas accessibility of the very thin porous film.

Nanoporous aluminum oxide micropatterns prepared by hydrogel templating - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanotechnology)
Micropatterned nanoporous aluminum oxide arrays are prepared on silicon wafer substrates by using photopolymerized poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel micropatterns are fabricated by spreading the prepolymer mixture on the substrate, followed by UV photopolymerization through a micropatterned mask. The hydrogel is covalently bonded to the substrate surface. Al2O3 is produced by swelling the hydrogel in a saturated aluminum nitrate solution and subsequent thermal conversion/calcination. As a result, micropatterned porous Al2O3 microdots with heights in µm range and large specific surface areas up to 274 m2 g−1 are obtained. Hence, the hydrogel fulfills a dual templating function, namely micropatterning and nanoporosity generation. The impact of varying the photopolymerization time on the properties of the products is studied. Samples are characterized by light and confocal laser scanning microscopy, scanning electron microscopy, energy-dispersive x-ray spectrometry, and Kr physisorption analysis.

Synthesis of Metal Oxide Inverse Opals from Metal Nitrates by PMMA Colloidal Crystal Templating - Zhang, Xuyang; Weinberger, Christian; Amrehn, Sabrina; Wu, Xia; Tiemann, Michael; Wagner, Thorsten (European Journal of Inorganic Chemistry)
Metal oxide inverse opals are interesting for various applications. To achieve highly ordered inverse opal structures, one important issue during the colloidal crystal templating procedure is to form a stable precursor network before the template loses its structural integrity at high temperature. Using poly(methyl methacrylate), PMMA, colloidal crystal templates, it is essential to consider the physical and chemical changes of the precursors induced by the changes of PMMA during the thermal conversion. For a systematic investigation of this matter, we synthesized a variety of metal oxide inverse opals from the respective metal nitrates, including Cr2O3, Ga2O3, Fe2O3, In2O3, CuO, CeO2, and ZnO, to compare the effect of various modifications of precursors on the structural and optical properties. When the nitrate precursors have a lower thermal stability than the PMMA template, we have modified the metal nitrates by chelating or by polyacrylamide gelation to form more stable precursor networks.

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Functional Nanoporous Materials - Weinberger, Christian; Tiemann, Michael (Nanomaterials)
This Special Issue on “Functional Nanoporous Materials” in the MDPI journal nanomaterials features seven original papers ...

Kleider in Bewegung. Frauenmode seit 1850 - Kraft, Kerstin

Water-based primary cell for powering of wireless sensors - Petrov, Dmitry; Hilleringmann, Ulrich (2020 IEEE SENSORS)

Musikwissenschaft und Theologie im Dialog - Johann Sebastian Bachs "h-Moll-Messe" und "Johannes-Passion"
Die h-Moll-Messe und die Johannes-Passion sind unzweifelhaft zwei Hauptwerke Johann Sebastian Bachs. Der vorliegende Band versammelt die Vorträge aus zwei Symposien, die im Oktober 2017 und März 2019 in Essen abgehalten worden sind. Im Dialog zwischen Theologie und Musikwissenschaft werden in den Beiträgen unterschiedliche Aspekte fokussiert, die je nach Werk zum einen eher auf dem Gebiet der Genese, Rezeption und Edition (h-Moll-Messe), zum anderen eher auf dessen theologischem oder musikgeschichtlichem Kontext (Johannes-Passion) liegen. In dieser interdisziplinären Zusammenstellung werden zahlreiche neue Facetten der Werke und ihrer Kontexte erhellt.

Die h-Moll-Messe szenisch: Rosamund Gilmore (1986), Achim Freyer (1996) und Jochen Biganzoli (2017) - Höink, Dominik (Musikwissenschaft und Theologie im Dialog - Johann Sebastian Bachs "h-Moll-Messe" und "Johannes-Passion")

Zur Stabilisierung medienbezogener Handlungsroutinen im Lehrer*innenberuf. Längsschnittliche Betrachtungen zur Integration von Tablets in den Arbeitsalltag - Dehmel, Lukas; Gerhardts, Lara; Meister, Dorothee M. (Mobile Medien im Schulkontext)

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Shnayien, Marie-Luise

Explorations in Digital Cultures

Reparaturbetrieb, Inklusion und Fachkräftesicherung Transformation der Benachteiligtenförderung in Deutschland. - Heisler, Dietmar (Historische Berufsbildungsforschung Perspektiven auf Wissenschaftsgenese und -dynamik.)
Jeder Wissenschaftsdisziplin hilft ein Bewusstsein ihrer Geschichte und die Kenntnis ihrer Vielfalt, Paradigmen und Entwicklungsmöglichkeiten. Darauf basierend können Forschende ihr spezifisches Potential, Wissen und Handlungsrepertoire entfalten. Dabei ist Geschichtsschreibung und historische Berufsbildungsforschung immer zugleich selbst gefangen in ihrer je eigenen Zeit, beschränkt durch die Perspektiven der Personen, die sich an dem Rückblick beteiligen. Das macht Geschichte auch immer zur Geschichte der Herrschenden, die eine spezifische Perspektive und die mit ihr verbundene Forschung schreibend tradieren. Deshalb ist Vielfalt für die historische Berufsbildungsforschung so wertvoll, weil sie sich gegen verengte, eindimensionale Retrospektive stellt, gewissermaßen in die Ritzen und Fugen der Zeit schauen lässt. Basierend auf einer Tagung der Herausgeber im September 2019 zu „Retrospektiven, Perspektiven & Synergien einer Historischen Berufsbildungs- und Wissenschaftsforschung" an der Universität Rostock, entfaltet sich die Bandbreite der historischen Berufsbildungsforschung. Der Band vereint paradigmatische, mal stärker biografischen Zugänge sowie systemisch-gesellschaftspolitische und schließlich Analysen zur Genese der Wissenschaftsdisziplin. In den Beiträgen wird dem Einfluss von Einzelpersönlichkeiten und Forschungsparadigmen ebenso wie dem von Bildungssystemen am Beispiel der DDR, Skandinaviens und der bundesdeutschen Bildungspolitik nachgegangen. Vereint sind sowohl Beiträge zur Entstehung der Berufs- und Wirtschaftspädagogik, zur Rekonstruktion der Benachteiligtenförderung, Soziökonomie, Pflegedidaktik und Frauenforschung als auch Analysen berufsspezifischer Betrachtungen am Beispiel des Druckgewerbes, der Offiziere und der Ausbilder*innen.
Keywords: Benachteiligtenförderung; historische Berufsbildungsforschung; berufliche Förderung; Sozialpädagogik

(Un)Sicherheitsproduktion im Cyberspace. Cybersecurity-Architekturen in Deutschland und der Schweiz - Hälterlein, Jens (TATuP)

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen und der Stellenwert einer Fachlichkeitskonzeption von Lehrenden der Fächergruppe Erziehungswissenschaft - Engemann, Mario

Gero Fuchs: Gewinn als Umbruch der Ordnung? Der Fall des Siegburger Töpfers Peter Knütgen im 16. Jahrhundert, Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Laura Schmidt: Weihnachtliches Theater. Zur Entstehung und Geschichte einer bürgerlichen Fest- und Theaterkultur, Bielefeld 2017 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Inklusion und Intersektionalität im Kontext frühkindlicher Medienbildungsforschung. Sprachkulturelle Homogenität und Diversität sowie ihre Auswirkungen auf pädagogische Kommunikation in der Frühen Bildung - Günesli, Habib (QfI - Qualifizierung für Inklusion Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Dieser Beitrag basiert auf den Ergebnissen eines im Jahr 2019 abgeschlossenen Promotionsvorhabens im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang zu den Mediensozialisationsbedingungen von deutschen, deutsch-türkischen und deutsch-anderen vier und fünf Jahre alten Mädchen und Jungen in den sozialen Feldern Familie und Kita. Im vorliegenden Beitrag wird auf die Befragung der ErzieherInnen fokussiert, die mittels halbstandardisierter Fragebögen durchgeführt wurde. Untersucht wurde, wie sich der sprachlich-kulturelle Hintergrund der Kinder für das Kommunikationsverhalten der ErzieherInnen mit den Kindern in pädagogischer Anschlusskommunikation und in Gesprächen mit den Eltern der Kinder auswirkt. Hier wurde auch eine intersektionale Perspektive eingenommen und parallel zur Herkunftskultur auch das biologische Geschlecht der Kinder in die Auswertung einbezogen. Es stellte sich heraus, dass die Kommunikation sowohl mit den Kindern als auch mit den Eltern in Abhängigkeit der Herkunftskultur der Kinder und auch ihres Geschlechtes erfolgt. Pädagogisch ist zu fragen, inwiefern es den pädagogischen Fachkräften gelingt, benachteiligende Ausgangslagen auch tatsächlich auszugleichen und Partizipation im Sinne von Inklusion zu ermöglichen. Ausgehend von diesen Ergebnissen wird in diesem Beitrag die Bedeutung und Relevanz der Überschneidungen und Interdependenzen von Ungleichheitsdimensionen für eine inklusionsorientierte Qualifikation pädagogischer Fachkräfte in institutionell-frühkindlichen Medienbildungskontexten diskutiert. Konkret richtet sich der Blick auf die sprachlich-kulturelle Ein- und Vielfalt in den frühkindlichen Einrichtungen sowie die Wahrnehmungen und Einschätzungen der pädagogischen Fachkräfte, die sie in Hinblick auf die Kooperationswilligkeit der Eltern, die Anschlusskommunikation mit den Kindern und schließlich die medialen Fähig- und Fertigkeiten der Kinder äußern.

Regularizing neural networks with gradient monitoring - Chadha, Gavneet Singh; Meydani, Elnaz; Schwung, Andreas (Recent Advances in Big Data and Deep Learning: Proceedings of the INNS Big Data and Deep Learning Conference INNSBDDL2019, held at Sestri Levante, Genova, Italy 16-18 April 2019)

Probing nonclassicality with matrices of phase-space distributions - Bohmann, Martin; Agudelo, Elizabeth; Sperling, Jan (Quantum)
We devise a method to certify nonclassical features via correlations of phase-space distributions by unifying the notions of quasiprobabilities and matrices of correlation functions. Our approach complements and extends recent results that were based on Chebyshev's integral inequality \cite{BA19}. The method developed here correlates arbitrary phase-space functions at arbitrary points in phase space, including multimode scenarios and higher-order correlations. Furthermore, our approach provides necessary and sufficient nonclassicality criteria, applies to phase-space functions beyond s-parametrized ones, and is accessible in experiments. To demonstrate the power of our technique, the quantum characteristics of discrete- and continuous-variable, single- and multimode, as well as pure and mixed states are certified only employing second-order correlations and Husimi functions, which always resemble a classical probability distribution. Moreover, nonlinear generalizations of our approach are studied. Therefore, a versatile and broadly applicable framework is devised to uncover quantum properties in terms of matrices of phase-space distributions.

Classical evolution in quantum systems - Sperling, Jan; Walmsley, I A (Physica Scripta)

Transfer function replacement of phenomenological single-mode equations in semiconductor microcavity modeling - Carcamo, M.; Schumacher, Stefan; Binder, R. (Applied Optics)
Semiconductor microcavities are frequently studied in the context of semiconductor lasers and in application-oriented fundamental research on topics such as linear and nonlinear polariton systems, polariton lasers, polariton pattern formation, and polaritonic Bose–Einstein condensates. A commonly used approach to describe theoretical properties includes a phenomenological single-mode equation that complements the equation for the nonlinear optical response (interband polarization) of the semiconductor. Here, we show how to replace the single-mode equation by a fully predictive transfer function method that, in contrast to the single-mode equation, accounts for propagation, retardation, and pulse-filtering effects of the incident light field traversing the distributed Bragg reflector (DBR) mirrors, without substantially increasing the numerical complexity of the solution. As examples, we use cavities containing GaAs quantum wells and transition-metal dichalcogenides (TMDs).
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

Realization of all-optical vortex switching in exciton-polariton condensates - Meier, Torsten; Ma, Xuekai; Berger, Bernd; Aßmann, Marc; Driben, Rodislav; Schneider, Christian; Höfling, Sven; Schumacher, Stefan (Nature communications)
Vortices are topological objects representing the circular motion of a fluid. With their additional degree of freedom, the vorticity, they have been widely investigated in many physical systems and different materials for fundamental interest and for applications in data storage and information processing. Vortices have also been observed in non-equilibrium exciton-polariton condensates in planar semiconductor microcavities. There they appear spontaneously or can be created and pinned in space using ring-shaped optical excitation profiles. However, using the vortex state for information processing not only requires creation of a vortex but also efficient control over the vortex after its creation. Here we demonstrate a simple approach to control and switch a localized polariton vortex between opposite states. In our scheme, both the optical control of vorticity and its detection through the orbital angular momentum of the emitted light are implemented in a robust and practical manner.

k.p-based multiband simulations of non-degenerate two-photon absorption in bulk GaAs - Hannes, Wolf-Rüdiger; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIV)

Strongly nonresonant four-wave mixing in semiconductors - Hannes, W.-R.; Trautmann, Alexander; Stein, M.; Schäfer, F.; Koch, M.; Meier, Torsten (Physical Review B)

Enhanced high-order harmonic generation in semiconductors by excitation with multicolor pulses - Song, Xiaohong; Yang, Shidong; Zuo, Ruixin; Meier, Torsten; Yang, Weifeng (Physical Review A)

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Generationelle und gesellschaftliche Differenzen im wiedervereinigten Deutschland - "Der neunzigste Geburtstag. Ein ländliches Idyll" von Günter de Bruyn in postkolonialer Lesart. - Müller, Inez

Transmediale und transkulturelle Schreibweisen im Exil der Gegenwart - Prosa und Lyrik syrischer Autoren in Europa - Müller, Inez (Peter Weiss Jahrbuch)

The Influence of Hydrothermal Aging on the Material Properties of Continuous Fiber-Reinforced Thermoplastics and its Non-Destructive Characterization - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Advances in Polymer Processing 2020)

Modeling and Optimization of Rectangular Latent Heat Storage Elements in an Air-Guided Heat Storage System - Grabo, Matti; Staggenborg, Christoph; Philippi, Kai Alexander; Kenig, Eugeny (Frontiers in Energy Research)

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Morbach, A.; Neukötter, Moritz; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
The influence of latent heat storage elements on the cooling performance and the temperature rise time of household refrigerating appliances is studied experimentally in the context of the “new global refriger- ator standard”IEC 62552:2015. In addition to the daily energy consumption, this international standard- ization introduced performance tests for cooling capacity and temperature rise time. While the cooling capacity has long been anchored in various test procedures of consumer organizations, the temperature rise time, which has only been tested on freezers so far, will be a decisive factor in the future. Moreover, the need for so-called "smart appliances" that may balance power consumption is increasing since such devices may compensate the volatility of renewable energies and thus stabilize the power grid. Against this background, eight commercial household refrigerators and refrigerator-freezers are equipped with polymer-bound phase change materials (PCM) and their performance is determined under the new stan- dard test conditions. The results show that the introduction of PCM increases the cooling capacity by up to 33 % and also increases the temperature rise time by up to 145 %, without affecting power consump- tion, as compared to the unmodified refrigeration appliances.

Age-related efficiency loss of household refrigeration appliances: Development of an approach to measure the degradation of insulation properties - Hueppe, Christian; Geppert, Jasmin; Stamminger, Rainer; Wagner, Hendrik; Hoelscher, Heike; Vrabec, Jadran; Paul, Andreas; Elsner, Andreas; Becker, Wolfgang; Gries, Ulrich; Freiberger, Alfred (Applied Thermal Engineering)
Despite the omnipresence of household refrigeration appliances, there is still a lack of knowledge about their agerelated efficiency loss over time. Past studies provide basic evidence for increasing electricity consumption of cooling appliances with ageing but fail to investigate the associated technical wear. Concentrating on the degradation of the thermal insulation, we first determined the ageing process of sealed samples of polyurethane rigid foam by investigating changes in cell gas composition and thermal conductivity over time. Simultaneously, the main challenge was to develop an approach that investigates the age-related efficiency loss of the insulation without its destruction. This testing procedure is referred to as the Bonn method. The non-destructive Bonn method was applied to varying refrigerator models in a series of successive experiments to evaluate the insulation degradation over time. Subsequently, the physical relationship between the test value of the Bonn method and the heat transfer through the multi-layered compartment walls of domestic refrigeration appliances was established, ultimately characterising the degrading insulation in terms of increasing heat transfer. Our results give substantiated evidence that the efficiency loss of cooling appliances is greatly influenced by insulation degradation over time. The ageing of sealed samples of polyurethane rigid foam indicates a large initial increase of thermal conductivity by 15% within the first year, corresponding to a change in cell gas composition. These results are in line with those of the Bonn method, emphasising an increasing heat flow through the multi-layered compartment walls of domestic refrigerators with ageing. Therewith, the present study is of significance to a wide range of stakeholders and forms the basis for future research.

Influence of the process temperature on the forming behaviour and the friction during bulk forming of high nitrogen steel
Due to the trend towards lightweight design in car body development mechanical joining technologies become increasingly important. These techniques allow for the joining of dissimilar materials and thus enable multi-material design, while thermic joining methods reach their limits. Semi-tubular self-piercing riveting is an important mechanical joining technology. The rivet production, however, is costly and time-consuming, as the process consists of several process steps including the heat treatment and coating of the rivets in order to achieve an adequate strength and corrosion resistance. The use of high nitrogen steel as rivet material leads to the possibility of reducing process steps and hence increasing the efficiency of the process. However, the high tool loads being expected due to the high strain hardening of the material are a major challenge during the rivet production. Thus, there is a need for appropriate forming strategies, such as the manufacturing of the rivets at elevated temperatures. Prior investigations led to the conclusion that forming already at 200 °C results in a distinct reduction of the yield strength. To create a deeper understanding of the forming behaviour of high nitrogen steel at elevated temperatures, compression tests were conducted in a temperature range between room temperature and 200 °C. The determined true stress – true strain curves are the basis for the further process and tool design of the rivet production. Another key factor for the rivet manufacturing at elevated temperatures is the influence of the process temperature on the tribological conditions. For this reason, ring compression tests at room temperature and 200 °C are carried out. The friction factors are determined on the basis of calibration curves resulting from the numerical analysis of the ring compression process. The investigations indicate that the friction factor at 200 °C is significantly higher compared to room temperature. This essential fact has to be taken into account for the process and tool design for the rivet production using high nitrogen steel.
Keywords: High nitrogen steel; Self-piercing riveting; Joining by forming; Bulk forming; Strain hardening

Improvement of a rivet geometry for the self-piercing riveting of high-strength steel and multi-material joints - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)
As a result of lightweight design, increased use is being made of high-strength steel and aluminium in car bodies. Self-piercing riveting is an established technique for joining these materials. The dissimilar properties of the two materials have led to a number of different rivet geometries in the past. Each rivet geometry fulfils the requirements of the materials within a limited range. In the present investigation, an improved rivet geometry is developed, which permits the reliable joining of two material combinations that could only be joined by two different rivet geometries up until now. Material combination 1 consists of high-strength steel on both sides, while material combination 2 comprises aluminium on the punch side and high-strength steel on the die side. The material flow and the stress and strain conditions prevailing during the joining process are analysed by means of numerical simulation. The rivet geometry is then improved step-by-step on the basis of this analysis. Finally, the improved rivet geometry is manufactured and the findings of the investigation are verified in experimental joining tests.
Keywords: Self-piercing riveting; Joining technology; Rivet geometry; Multi-material design; High-strength steel; Aluminium

A micromechanical-based finite element simulation of process-induced residual stresses in metal-CFRP-hybrid structures - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Composite Structures)

Probability Distribution of Joint Point Loadings in Car Body Structures under Global Bending and Torsion - Martin, Sven; Camberg, Alan A.; Tröster, Thomas (Procedia Manufacturing)

CFD Simulation of Film and Rivulet Flows on Microstructured Surfaces - Bertling, René; Hack, Mathias; Ausner, Ilja; Kenig, Eugeny

Microstructural investigation on phase transformation during flow forming of the metastable austenite AISI 304 - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (54. Metallographie-Tagung)

Realization of all-optical vortex switching in exciton-polariton condensates - Ma, Xuekai; Berger, B; Aßmann, M; Driben, R; Meier, Torsten; Schneider, C; Höfling, S; Schumacher, Stefan (Nature Communications)

Federico Fellini’s Sanctifying Effect. - Ahrens, Stephan (Journal of Italian Cinema & Media Studies 9, Nr. 1)

Vom Klang bewegt. Das Kino und Ludwig van Beethoven. - Ahrens, Stephan

Offensive Sensation. Ein Porträt von Melina Mercouri - Ahrens, Stephan (Dschungel (jungle World))